2003
DOI: 10.1088/0963-0252/13/1/005
|View full text |Cite
|
Sign up to set email alerts
|

Time resolved diagnostics and kinetic modelling of a modulated hollow cathode discharge of NO2

Abstract: The transients associated with the ignition and the extinction of the cold plasma produced in a low frequency, square-wave modulated, hollow cathode discharge of nitrogen dioxide are characterized by time resolved emission spectroscopy, mass spectrometry and electrical probes. The temporal evolution of the concentrations of neutral species created or destroyed in the NO 2 discharges are compared with the predictions of a simple kinetic model previously developed for discharges of other nitrogen oxides (N 2 O a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…In previous publications, the authors have demonstrated how the employment of modulation techniques facilitates the distinction among processes, relevant in different time scales, for N 2 O [23,24], NO 2 [25] and air plasmas [26]. Time-resolved spectroscopy for the observation of molecular [23,24] or atomic species [25,26] in combination with kinetic modeling of the modulated discharges allowed to clarify the most important reactions [23,24] or the estimation of rate coefficients [26] in those plasmas. In this work, a similar procedure is followed to get further details in H 2 + 10% N 2 plasmas by using low frequency modulation, together with a recently developed kinetic model [8] that accounted quite satisfactorily for stationary state results.…”
Section: Introductionmentioning
confidence: 99%
“…In previous publications, the authors have demonstrated how the employment of modulation techniques facilitates the distinction among processes, relevant in different time scales, for N 2 O [23,24], NO 2 [25] and air plasmas [26]. Time-resolved spectroscopy for the observation of molecular [23,24] or atomic species [25,26] in combination with kinetic modeling of the modulated discharges allowed to clarify the most important reactions [23,24] or the estimation of rate coefficients [26] in those plasmas. In this work, a similar procedure is followed to get further details in H 2 + 10% N 2 plasmas by using low frequency modulation, together with a recently developed kinetic model [8] that accounted quite satisfactorily for stationary state results.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the possible NO ↔ NO 2 conversion channels showed that in O 2 plasma NO can be oxidized into NO 2 via reactions R1 and R2, but this oxidation is balanced by an efficient inverse process R3 (see Table 2) [3,5]. Heterogeneous oxidation of NO by O atoms may also take place, but this reaction is much slower than R1-R2 as it was found in [21,22]. Furthermore, reaction R2 may be ignored because in low pressure oxygen discharge conditions concentration of O 3 is too low [23] .…”
Section: Kinetics Of Nitrogen Oxidesmentioning
confidence: 93%
“…Diffusion of excited species to the cathode walls, where they might collide and experiment de‐excitation, is described by Fick's Law [ Levine , ; McDaniel , ]. We have assumed a model of rigid spheres and employed the effective diameters of N 2 and O 2 from Hirschfelder et al [] to estimate the typical diffusion times along the cathode radius, as it was done in Castillo et al [], Castillo et al [], and de los Arcos et al []. Under the present air pressures ranging from 0.1 to 2 mbar, these diffusion times result to be within the interval 0.1–1 ms, considerably longer than the radiative lifetimes of the excited N 2 and normalN2+ levels in this work, whereas the average time between successive collisions at these pressures (equivalent to some 68–50 altitudes) are of some 10 −6 –10 −7 s, respectively [ McDaniel , ].…”
Section: Methodsmentioning
confidence: 99%